Influence of Carbonate Solvents on Solid Electrolyte Interphase Composition over Si Electrodes Monitored by In Situ and Ex Situ Spectroscopies - Wu, Zhan-Yu; Lu, Yan-Qiu; Li, Jun-Tao; Zanna, Sandrine; Seyeux, Antoine; Huang, Ling; Sun, Shi-Gang; Marcus, Philippe; Światowska, Jolanta (ACS omega, 2021)
A solid electrolyte interphase (SEI) layer on Si-based anodes should have high mechanical properties to adapt the volume changes of Si with low thickness and good ionic conductivity. To better understand the influence of carbonate solvents on the SEI composition and mechanism of formation, systematic studies were performed using dimethyl carbonate (DMC) or propylene carbonate (PC) solvent and LiPF6 as a salt. A 1 M LiPF6/EC-DMC was used for comparison. The surface chemical composition of the Si electrode was analyzed at different potentials of lithiation/delithiation and after a few cycles. Ex situ X-ray photoelectron spectroscopy and time-of-flight secondary ion mass spectrometry results demonstrate that a thinner and more stable SEI layer is formed in LiPF6/DMC. The in situ Fourier transform infrared spectroscopy proves that the coordination between Li+ and DMC is weaker, and fewer DMC molecules take part in the formation of the SEI layer. The higher capacity retention during 60 cycles and less significant morphological modifications of the Si electrode in 1 M LiPF6/DMC compared to other electrolytes were demonstrated, confirming a good and stable interfacial layer. The possible surface reactions are discussed, and the difference in the mechanisms of formation of SEI in these three various electrolytes is proposed.